PENDAMPINGAN PENGGUNAAN APLIKASI AKUNTANSI DAN PEMASARAN BERBASIS ANDROID (e LEATHERSGOOD.ID) PADA KELOMPOK UMKM TAS GOLF DAN KERAJINAN KULIT DESA KALITENGAH SIDOARJO - Duwi Rahayu; Hamzah Setiawan; Alshaf Pebrianggara (Jurnal Abdi Insani, 2023)
The MSME group of golf bags and leather handicrafts of Kalit tengah Sidoarjo village is one of the groups affected by covid 19. The MSME group has difficulties in terms of accounting and marketing records which have an impact on the development of MSMEs. The MSME group sometimes finds it difficult in terms of android-based marketing and the thought "this is how it's just not going to be weird". In this regard, assistance will be carried out regarding accounting and marketing records using e-leathergoods.id to the managers of the Golf Bag MSME group and leather handicrafts. The purpose of this community service activity is to improve the quality of systematic android-based accounting and marketing records for the sake of increasing professionalism and can be the basis for conducting profit / loss analysis per month. Activity method: The implementation of this assistance will use the focus group discussion method, through this assistance it is expected to provide benefits in recording android-based accounting and marketing using e-leathergoods.id for the MSME group of Golf Bags and Leather Handicrafts of Kalit tengah Village Tanggulangin Sidoarjo. The result of this community service activity is that the Managers of the Golf Bag MSME group and leather handicrafts of Kalit tengah Sidoarjo Village are able to operate the leathesgood.id application in financial management and marketing through continuous assistance. In conclusion, the manager of the Golf Bag MSME group and leather handicrafts of Kalit tengah Sidoarjo Village through the leathesgood.id application has been able to carry out quality accounting and marketing records both conventionally and through android-based applications. This android Leathersgood.id application can be integrated with direct marketing so that the managers of The Golf Bag And Leather Handicraft MSME group can find out the number of sales transactions in real time and profit / loss per month.